(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The electrocoagulation (EC) process has emerged as a viable alternative for treating textile effluent before its release into the environment. However, a notable limitation of this method is the requirement for frequent replacement of the sacrificial anode, leading to elevated costs associated with electrode material. Thus, this research aims to conduct a comparative study between waste steel containers (WSC) and commercially available iron (Fe) electrodes in terms of electrochemical behaviour that significantly influences the EC performance in treating Acid Red 18 (AR18) dye. The electrochemical experiments were performed using an electrochemical analyser, followed by a batch EC experiment for AR18 dye removal. The results indicate that the WSC electrode has a more negative corrosion potential, Ecorr value of -0.954 V vs. SCE, compared to Commercial Pure Iron (CPI) at -0.947 V vs. SCE and Commercial Mild Steel (CMS) at -0.908 V vs. SCE. This suggests that WSC is more susceptible to corrosion, leading to a higher dissolution rate of Fe ions than the commercial electrodes. The findings were also in line with the EC performance, where the removal efficiency of the WSC electrode (99.7%) was found to be slightly higher than that of the commercial electrodes of CMS (98.7%) and CPI (98.1%). In conclusion, the utilization of WSC has demonstrated its efficacy as an electrode option to serve as an alternative to conventional Fe electrodes in the treatment of AR18 dye solutions.